To Retain or Resurface the Patella in Primary Total Knee Arthroplasty: A Comparative Study - Larry Rodrigues De Campos Júnior; Guilherme Norberto Sbalqueiro; Ruben Amancio Rojas Ayala; Osmar Valadão Lopes Junior; Paulo Renato Fernandes Saggin; Andre Kuhn (Revista Brasileira de Ortopedia, 2022)
Abstract Objective To evaluate and compare clinically and functionally patients undergoing primary total knee arthroplasty (TKA) with preservation or replacement of the patella. Methods In a cross-sectional study, the functional results were evaluated and compared, using the Western Ontario and McMaster Universities (WOMAC) and Lequesne scores, of 158 patients undergoing primary TKA (162 knees); in 81 knees the patella was submitted to arthroplasty and in 81 the joint surface of the patella was preserved. Results No significant differences were identified in terms of the Lequesne score (p = 0.585), global WOMAC score (p = 0.169), nor in terms of its subdivisions regarding stiffness (p = 0.796) and functional capacity (p = 0.190). There was a significant difference only in terms of the subdivision that evaluates pain in the WOMAC score, being lower in the group undergoing patellar arthroplasty (p = 0.036). Conclusion In the present study, there was no difference in functional assessment in patients who underwent or not patellar replacement during primary knee arthroplasty surgery. However, individuals in whom the patella was preserved reported more pain.